2009
DOI: 10.3945/ajcn.2008.27335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fat saturation on satiety, hormone release, and food intake

Abstract: When infused into the ileum, triacylglycerols with unsaturated fatty acids increase satiety, whereas triacylglycerols with saturated fatty acids does not. This trial was registered with the Dutch Trial Register as: ISRCTN51742545.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
5
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 33 publications
6
91
5
5
Order By: Relevance
“…Boyd et al (2003) found that following a 2-week HF or LF diet, hunger was greater during an oral fat tolerance test following the HF diet; however, this did not affect subsequent food intake. Similarly, ileal infusion of fatty acids 18:1 or 18:2, but not 18:0, reduced appetite but not food intake (Maljaars et al, 2009). Park et al (2007) found no changes in GI transit or appetite following an HF diet intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boyd et al (2003) found that following a 2-week HF or LF diet, hunger was greater during an oral fat tolerance test following the HF diet; however, this did not affect subsequent food intake. Similarly, ileal infusion of fatty acids 18:1 or 18:2, but not 18:0, reduced appetite but not food intake (Maljaars et al, 2009). Park et al (2007) found no changes in GI transit or appetite following an HF diet intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the volunteers were subjected to a narrow range of fatty acids from sunflower oil, primarily linoleic acid (LA; 18:2). It is known that the GI tract responds very specifically to different fatty acids (Robertson et al, 2002;Maljaars et al, 2009). Any adaptation is hence going to be specific to the effects of that fatty acid.…”
Section: Discussionmentioning
confidence: 99%
“…Maljaars et al (121) reported no differences in PYY levels in normal-weight adults (men and women) following infusions of MUFA, PUFA or SFA. It is important to note that these were infusions of fatty acids via a naso-ileal catheter and not oral consumption of foods containing those fatty acids.…”
Section: Dietary Fatty Acids and Peptide Yymentioning
confidence: 99%
“…Nevertheless, proteins from different sources vary in their effects on satiety (9,10) , and fats can vary in effects on satiety due to differences in chain length, degree of unsaturation and configuration of the fatty acids and differences in the composition and stability of emulsions (11)(12)(13)(14)(15) . Dietary fibre components are also very variable in chemical and physical characteristics and can influence satiety by a range of mechanisms.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%